2006
DOI: 10.1517/17425247.3.5.693
|View full text |Cite
|
Sign up to set email alerts
|

New advances in aerosolised drug delivery: vibrating membrane nebuliser technology

Abstract: Innovative nebuliser systems bear the potential to greatly improve and expand the administration of therapeutic aerosols for the treatment of respiratory diseases. Exploiting the technology of a microperforated vibrating membrane offers a close control of the droplet size that is being generated and targeted to reach the lower airways, with little oropharyngeal deposition, thereby reducing undesired side effects. The greatly improved efficiency of such devices, as exemplified by the eFlow nebuliser (PARI), pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 6 publications
1
33
1
2
Order By: Relevance
“…However, the vibrating mesh plat consists of a piezoelectric element fixed at the bottom of the nebulizer chamber that vibrates in response to electric current [6,18,19]. Upward and downward movement of vibrating plat convert respirable solution in nebulizer chamber to fine droplets emitted out toward patient [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the vibrating mesh plat consists of a piezoelectric element fixed at the bottom of the nebulizer chamber that vibrates in response to electric current [6,18,19]. Upward and downward movement of vibrating plat convert respirable solution in nebulizer chamber to fine droplets emitted out toward patient [20].…”
Section: Discussionmentioning
confidence: 99%
“…Pari: The eFlow mesh nebulizer was approved for sale in 2004 [24]. The original eFlow nebulizer, designed by Pari GmbH using The Technology Partnership plc mesh technology, had an active mesh with a gravity liquid feed, aerosol reservoir chamber and inhalation and exhalation valves [25].…”
Section: Mesh Nebulizer Manufacturersmentioning
confidence: 99%
“…Basic aperture templates (i.e., eFlowrapid nebulizer membranes [Knoch and Keller 2005;Lass et al 2006]) containing tapered holes with large cross-sections (»30 mm) on the reservoir side and narrow cross-sections (»5 mm) on the side from where the aerosol droplets emerge (Beck-Broichsitter et al 2014a) ( Figure 1a) were coated by a polymer deposit, where the opening cross-section of the orifices was then determined by the applied polymer coating layer thickness. Conformal polymer films on membrane templates were achieved by CVD with PPXC (trade name parylene C) (Lahann 2006;Gazicki-Lipman 2007).…”
Section: Resultsmentioning
confidence: 99%
“…These devices reveal potential to overcome the main shortcomings associated with "traditional" pneumatic-and ultrasound-driven nebulizers (Beck-Broichsitter et al 2012) and moreover, were shown to be suitable for aerosolization of sensitive molecules such as proteins (Germershaus et al 2013) and advanced drug-delivery vehicles like liposomes (Beck-Broichsitter et al 2013a) and polymeric nanoparticles (Beck-Broichsitter et al 2013b). Microscale orifice dimensions are required for the generation of fine medicament mists suitable for inhalation to the deep lungs (Knoch and Keller 2005;Lass et al 2006). However, the fabrication of perforations suitable for generating droplets <5 mm by standard techniques like microelectroforming (Shen et al 2008;Lin et al 2011) or laser drilling (Kohno and Matsuoka 2004;Geerken et al 2008) is challenging.…”
Section: Introductionmentioning
confidence: 99%